Pengamatan Tanaman Cabai (Capsicum annum L.) dan Tomat Ceri (Solanum lycopersicum var. Cerasiforme) pada Kekeringan - Gulo, Melvin; Komara, Riska; Meliawati, Vini; Damayanti, Welsi (Universitas Mataram, 2024)
Chili peppers and cherry tomatoes are important horticultural crops for the people of Indonesia. However, both plants are susceptible to drought stress. This study aims to determine the effect of drought on the growth of chili and cherry tomato plants. This research was conducted using the observation method for 3 weeks with no watering treatment. The results showed that both plants could not survive in drought conditions. Cherry tomato plants are more susceptible to drought than chili plants. The leaves of cherry tomato plants dry faster than chili plants, while the stems of chili plants are more resistant to drought than cherry tomato plants. The soil on both plants experienced aridity on the same day, which was on day 15. Based on the results of this study, it can be concluded that drought is a limiting factor for the growth of chili and cherry tomato plants. Therefore, adequate irrigation is an important factor in the cultivation of horticultural crops.